Titanium Oxide with Nanocoolant for Heat Exchanger Application - Kottasamy, A.; K., Kadirgama; Keeran, Annamalai; Mohanesan, K.; D., Ramasamy; M. M., Rahman; M. M., Noor; M. Razali, Hanipah (Faculty Mechanical Engineering, UMP, 2017)
The objective of this paper is to investigate the properties of oil-based nanofluids and produce stable and biodegradable oil-based nanofluids by metal oxide nanoparticles. The cooking oil was used as a base for the nanofluid preparation. Titanium oxide was embedded as the nanoparticles, mixed with cooking oil volume concentration of nanofluids specimens, and labelled as 0.01, 0.03, 0.05, 0.07, and 0.09. The study explained the analysis techniques applied to determine the enhancement of thermal properties of nanofluids. The thermal conductivity of nanofluids was studied by heat transfer rate and the overall heat transfer coefficient gained. The metal oxide nanomaterials were mixed with the oil-based fluids in order to prepare the specimens. This research focused on the usage of vegetable oil and titanium oxide nanoparticles mixture to form nanofluids. The results obtained indicated that the nanofluid gave better thermal conductivity than oil-based fluids. The results significantly increased the thermal properties limitation and improved the product reliability. The enhancement of heat transfer rate for 0.09% of nanofluid volume concentration was increased by 36.25%